Proyecto eco hotel Colibríes para un desarrollo eco turístico en el bosque Bavaria de Villavicencio-Meta (2021)
The theme of this work is developed in the Argentinean side of the road, the old road to Rest repo in the grounds of the Bavarian brewery in the municipality of Villavicencio (Meta). A strategic architectural project is generated for the region of the Llanos Orientals, proposing the design of an eco-hotel based on the natural wealth of the place and taking advantage of natural resources, which can make my project a sustainable proposal for the environment and society that inhabits it. Stop thinking that the land can only be worked by the farmer in the form of agriculture and livestock and evaluate how feasible and appropriate for the environment is the creation of alternative rural economies such as ecotourism.